Dual Functions of Natural Killer Cells in Selection and Differentiation of Stem Cells; Role in Regulation of Inflammation and Regeneration of Tissues - Jewett, Anahid (Ivyspring International Publisher, 2012)
Accumulated evidence from our laboratory indicates that conditioned or anergized NK cells have the ability to induce resistance of healthy stem cells and transformed cancer stem cells through both secreted factors and direct cell-cell contact by inducing differentiation. Cytotoxic function of NK cells is suppressed in the tumor microenvironment by a number of distinct effectors and their secreted factors. Furthermore, decreased peripheral blood NK cell function has been documented in many cancer patients. We have previously shown that NK cells mediate significant cytotoxicity against primary oral squamous carcinoma stem cells (OSCSCs) as compared to their more differentiated oral squamous carcinoma cells (OSCCs). In addition, human embryonic stem cells (hESCs), human mesenchymal stem cells (hMSCs), human dental pulp stem cells (hDPSCs) and induced human pluripotent stem cells (hiPSCs) were all significantly more susceptible to NK cell mediated cytotoxicity than their differentiated counterparts or parental cells from which they were derived. We have also reported that inhibition of differentiation or reversion of cells to a less-differentiated phenotype by blocking NFκB or gene deletion of COX2 significantly augmented NK cell function. Furthermore, the induction of resistance of the stem cells to NK cell mediated cytotoxicity and their subsequent differentiation is amplified when either the stem cells or the NK cells were cultured in the presence of monocytes. Therefore, we propose that the two stages of NK cell maturation namely CD16+CD56dimCD69- NK cells are important for the lysis of stem cells or poorly differentiated cells whereas the CD16dim/-CD56dim/+CD69+NK cells are important for differentiation and eventual regeneration of the tissues and the resolution of inflammation, thus functionally serving as regulatory NK cells (NK(reg)). CD16 receptor on the NK cells were found to be the receptor with significant potential to induce NK cell anergy, however, our recent data indicated that NKp46 but not NKp30 or NKp44 were also able to induce significant anergy in NK cells, although the levels were less when compared to CD16 receptor triggering. The concept of split anergy in NK cells and generation of NK(reg) and its contribution to cell differentiation, tissue repair and regeneration and in tumor resistance will be discussed in this review.